Kontribusi Minat Belajar Siswa Terhadap Hasil Belajar Pemograman Dasar Kelas XI Teknik Komputer Dan Jaringan Di SMK - Harahap, Syaiful Zuhri; Novita, Rini (Journal of Computer Science and Information System(JCoInS), 2023)
The research purpose to know the contribution of student interest for the leaning outcomes of basic program at the second year student of Computer Engineering and Networks at the SMK 2 Padang. At the year of study 2014/2015. The research problem is the leaning outcomes for the basic program lesson at the second year student is, there is still many of student knowledge level position below the minimum completeness criteria (KKM) given. The minimum completeness criteria standard for the SMK N 2 Padang with the range 0-100. But the fact only 92.72% of student got less than grades 7.28% of the student got more then 75 good. This research is quantitative with the type of research is correlational. That is the research to find out the level of correlation research variable with the differed contribution variable which is the contribution of independent variables on the dependent variable. The instrument used in collecting the data in this research is the questioner form and the leaning outcomes. To know the student interest, the writer used the questioner compiled with the Likert Scale models. The instrument leaning outcomes using the multiple choice (multiple choice item test). The research data analyzed by using correlation techniques. The analysis data by using the statistical program IBM SPSS computer Statistics 21. Â Based on the research that has been conducted of the research population are the students of second year of Computer Program and Networking at the SMK 2 Padang at the year of study 2014/2015 with 55 population students and used total sample of TKJ 1 and TKJ 2. So we can calculate that student interest the leaning outcomes is 79.49%. As the hypothesis test using correlation Pearson product moment between the student interest whit leaning outcomes is 0.572 and get the level t count and df=n-2 for the significant level of 0.05, whit the provisions t count more than t table, then compared it with t table so it can conclude that t count 5.083 bigger than 2.006 t table then Ho is reject and Ha is accepted, it means that there is correlation between student interest towards learning leaning outcomes.